Effects Of Palm Oil Mill Effluent On Seed Germination And Total Chlorophyll, Phenol And Carotene Contents Of Maize (Zea Mays L.) (Applied Biological Research, 2015)
Palm Oil Mill Effluent (POME) is produced in large quantities in Nigeria  and is amenable to microbial degradation. Studies were conducted to assess  the effect of various concentration of POME on germination, total chlorophyll, phenol and carotene contents of maize plant. Different concentrations  of POME tested were 0, 25, 50, 75 and 100% (prepared in water). Each  treatment was stored in separate container. Maize seeds were planted in 25  sterilized petri-plates and each treatment replicated five times. POME (10  mL) taken from a given concentration was used to irrigate the planted  seeds as per treatment at 48 h interval. Results revealed that theuse of 25%  POME gave highest seed germination and total chlorophyll content of 68%  and 17.56 mg mL-1, respectively while 100% POME gave 26% germination  nd 9.18 mg chlorophyll mL-1. The phenol content was highest in 75% POME and lowest in control. Carotenoid content in maize seedlings was  highest carotene in 50% POME treatment. The study revealed that POME at proper dilution could serve as a bio-fertilizer for seedling growth.
Keywords: Chlorophyll,maize; palm oilmill effluent; phenol; germination